1995
DOI: 10.1152/ajplung.1995.269.1.l78
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of thiazine dyes by bovine pulmonary arterial endothelial cells in culture

Abstract: The uptake of methylene blue (MB), and toluidine blue O (TBO) by bovine pulmonary arterial endothelial cells grown on microcarrier beads was detected as a decrease in the concentration of dye in the medium after these thiazine dyes were added to the medium surrounding the cells. Because the reduced forms of these dyes are much more lipophilic than the oxidized forms, we considered the possibility that reduction of the dyes at the cell surface might have preceded the uptake by the cells. Therefore, we studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 0 publications
2
58
0
Order By: Relevance
“…In its oxidized form, MB is blue in color and readily reduced by many living cells [14]. In order for MB to enter the cytosol, it is reduced at the exofacial cell surface into its colorless lipophilic form, leuko MB (MBH 2 ) [15]. Once inside the cell, this reduced MBH 2 can be re-oxidized to MB, which is trapped in the cell [16].…”
Section: Mb's Autoxidizable Mechanism Of Actionmentioning
confidence: 99%
“…In its oxidized form, MB is blue in color and readily reduced by many living cells [14]. In order for MB to enter the cytosol, it is reduced at the exofacial cell surface into its colorless lipophilic form, leuko MB (MBH 2 ) [15]. Once inside the cell, this reduced MBH 2 can be re-oxidized to MB, which is trapped in the cell [16].…”
Section: Mb's Autoxidizable Mechanism Of Actionmentioning
confidence: 99%
“…However, the clinical use of MB has been hampered by its propensity for rapid chemical alteration when systemically applied: MB in the biological environment is usually converted by accepting electrons from NADH/NADPH, and unfortunately, the formed colorless leukomethylene blue (LMB) has negligible photodynamic activity [11][12][13]. Recent studies suggested the presence of a transmembrane thiazine dye reductase at the cell surface as the initial factor for MB reduction [14][15][16]. Once within the cells, MB also can be reduced via NADH/NADPH dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, inhibitors are used to provide discriminating data relevant to these processes, and kinetic modeling is used to interpret such data and obtain values for kinetic parameters descriptive of the individual processes involved. Using this overall strategy, we have studied the impact of pulmonary endothelial cells on a variety of redox-active and other substances (4,12,13,38,40,41). The studies have revealed the wide range of pulmonary endothelial redox enzymes and other processes capable of influencing the metabolism, redox status, and disposition of compounds carried in the blood.…”
mentioning
confidence: 99%